Rapid differentiation of bacterial meningitides by direct gas-liquid chromatography. - Thadepalli, H (1982)
Rapid identification of Haemophilus influenzae and other bacillary meningitides was attempted by gas-liquid chromatography (GLC) of the metabolic by-products in broth cultures and in cerebrospinal fluid (CSF) samples obtained from experimental meningitis produced in New Zealand White male rabbits. These results were correlated with the GLC of CSF of meningitis patients. A major peak with retention time of succinic acid was found in the broth cultures of all bacilli tested including H. influenzae, Escherichia coli, Enterobacter cloacae, Klebsiella pneumoniae, Proteus mirabilis, Citrobacter freundii, Pseudomonas aeruginosa, and Listeria monocytogenes. Succinic acid was also found in the CSF of experimental meningitis and in the CSF of all patients with H. influenzae and Esch. coli meningitis. This peak was not detected in the blood samples of experimental animals. It was also absent in the broth cultures of all of the gram-positive and gram-negative cocci tested, such as Streptococcus pneumoniae and Neisseria meningitidis. Succinic acid, which appears to be a by product of fermentation, persisted as a clear cut marker in H. influenzae meningitis for at least 3 d after the initiation of treatment. In one patient, the succinic acid peak disappeared during treatment and reappeared with a clinical relapse. Clearly, the presence of succinic acid that can be rapidly detected by GLC in the CSF excludes pneumococcal or meningococcal meningitis and strongly suggests H. influenzae or other bacillary meningitides.